Electrophopretic variation in feral populations of three freshwater species of fish - Doyungan, Zaldy F. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 1998)
Analysis of hemoglobin and plasma esterase in the blood sample of three feral freshwater species of fish, namely, spotted gourami (Trichogaster trichoptenus)